Feliks Koneczny's historical and philosophical reflection on the concept of a nation - Bukowska, Sonia (Folia Philosophica, 2002)
The subject of the present article is the problem of a nation in the historical and philosophical conception of Feliks Koneczny, a Polish philosopher and historian living in the years 1862-1949. The main topic of the present study is preceded by a brief outline of the model conceptions of a nation, particularly the cultural and political models. The author’s analysis of F. Koneczny’s approach is opened by the question of treating a nation as an ethical superstructure of the society. Further on, the author tackles the problem of the factors which, in keeping with the discussed theory, are supposed to condition the formation of a nation. Taking into account the historical dimension of this phenomenon, the reflections of that philosopher of history, concerning the formation of modern nations, have been presented. Particular emphasis has been placed on the civilisational aspect of a nation, the concept of which, in F. Konieczny’s theory, was directly connected with the problem of one’s native country and native language. The article is closed with the author’s remarks on the presence of neo-Messianic motifs in the analysed concept of a nation.